Strong Immunity to Drain-Induced Barrier Lowering in ALD-Grown Preferentially Oriented Indium Gallium Oxide Transistors - Kim, Gwang-Bok; Kim, Taikyu; Bang, Seon Woong; Hur, Jae Seok; Choi, Cheol Hee; Kim, Min Jae; Jeong, Jae Kyeong (American Chemical Society, 2024)
Drain-induced barrier lowering (DIBL) is one of the most critical obstacles degrading the reliability of integrated circuits based on miniaturized transistors. Here, the effect of a crystallographic structure change in InGaO [indium gallium oxide (IGO)] thin-films on the DIBL was investigated. Preferentially oriented IGO (po-IGO) thin-film transistors (TFTs) have outstanding device performances with a field-effect mobility of 81.9 +/- 1.3 cm(2)/(V s), a threshold voltage (V-TH) of 0.07 +/- 0.03 V, a subthreshold swing of 127 +/- 2.0 mV/dec, and a current modulation ratio of (2.9 +/- 0.2) x 10(11). They also exhibit highly reliable electrical characteristics with a negligible V-TH shift of +0.09 (-0.14) V under +2 (-2) MV/cm and 60 degrees C for 3600 s. More importantly, they reveal strong immunity to the DIBL of 17.5 +/- 1.2 mV/V, while random polycrystalline In2O3 (rp-In2O3) and IGO (rp-IGO) TFTs show DIBL values of 197 +/- 5.3 and 46.4 +/- 1.2 mV/V, respectively. This is quite interesting because the rp- and po-IGO thin-films have the same cation composition ratio (In/Ga = 8:2). Given that the lateral diffusion of oxygen vacancies from the source/drain junction to the channel region via grain boundaries can reduce the effective length (L-eff) of the oxide channel, this improved immunity could be attributed to suppressed lateral diffusion by preferential growth. In practice, the po-IGO TFTs have a longer L-eff than the rp-In2O3 and -IGO TFTs even with the same patterned length. The effect of the crystallographic-structure-dependent L-eff variation on the DIBL was corroborated by technological computer-aided design simulation. This work suggests that the atomic-layer-deposited po-IGO thin-film can be a promising candidate for next-generation electronic devices composed of the miniaturized oxide transistors.